Penghilangan Tinta Kertas Koran Bekas dalam Pembuatan Papan Komposit Plastik - Afri Soni Wanson Samosir; Tito Sucipto; Lutfhi Hakim (Peronema Forestry Science Journal, 2015)
The objective of this research were to evaluate the effect of paper deinking on physical and mechanical properties of plastic composite board (fiber plastic composite). Deinking process using detergents with a concentration of 0%, 10%, 15%, 20%, and 25%. Clean pulp produced an acceptable material, while lathering ink that leaves the pulp was an rejected ingredient. The resulting composite board tested and their mechanical and physical properties compared to standard JIS A 5905-2003 hardboard S20 and JIS A 5908-2003 particleboards type 13. The results showed that the value of the density, moisture content, water absorption, thickness swelling, MOE, MOR, and IB were respectively from 0,61-0,69; 4,58-5,93; 29,62-39.81; 5,09-9,89; 0,96-1,22; 6,56-8,70; and 0,77-0,98. Testing that fulfill the standard requirement were testing the density, thickness swelling, and internal bond. Keywords: plastic composite board, polyethylene plastic, detergent concentration, physical and mechanical properties